2019
DOI: 10.7759/cureus.6392
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Immune Checkpoint Inhibitor Refractory Colitis Treated with Mycophenolate and High-dose Steroids

Abstract: Immune checkpoint inhibitors (ICPI) are a class of chemotherapy agents that have emerged as a front-line treatment option for multiple cancers. Nivolumab is an ICPI agent commonly used to treat metastatic melanoma. Although promising, the adverse reaction of this class is broad and per reports, the incidence of colitis is <6%. We present the case of a 71-year-old male with a history of metastatic melanoma who was being treated with nivolumab. The patient was two weeks into his treatment regimen when he began c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Randhawa et al [12] have recently presented the case of a 27-year-old female with severe colitis, refractory to methylprednisolone, infliximab and mycophenolate mofetil, who responded to vedolizumab, which is a humanized monoclonal antibody against α4β7 integrin [12]. On the other hand, Alcantar et al [13] presented the case of a patient in whom clinical remission was observed under steroids and mycophenolate after high-dose steroids, infliximab, and vedolizumab failed to achieve a resolution of the patients’ symptoms [13]. Nevertheless, we decided to keep our immunosuppression regime limited to steroids and infliximab because of the induction of a remarkable clinical remission, even though a daily mesalazine dose is necessary in order to preserve this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Randhawa et al [12] have recently presented the case of a 27-year-old female with severe colitis, refractory to methylprednisolone, infliximab and mycophenolate mofetil, who responded to vedolizumab, which is a humanized monoclonal antibody against α4β7 integrin [12]. On the other hand, Alcantar et al [13] presented the case of a patient in whom clinical remission was observed under steroids and mycophenolate after high-dose steroids, infliximab, and vedolizumab failed to achieve a resolution of the patients’ symptoms [13]. Nevertheless, we decided to keep our immunosuppression regime limited to steroids and infliximab because of the induction of a remarkable clinical remission, even though a daily mesalazine dose is necessary in order to preserve this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there are also other potential biologics for refractory ICI-related colitis (203). Anti-IL-1 blockade (anakinra), anti-IL-17 blockade (ixekizumab), anti-IL-23 and anti-IL-12 blockade (ustekinumab) (209), mycophenolate mofetil (MMF) (210,211), and ciclosporin (54), aiming at blocking critical inflammatory components participating in the pathophysiological process of irAEs, are reported to exert considerable effects in treating severe CIC. Besides, Janus kinase (JAK) inhibitors (tofacitinib) have shown efficacy in CIC patients (212).…”
Section: Biological Agentsmentioning
confidence: 99%
“…Although there are considerably less data, a systematic review showed equal efficacy of vedolizumab in comparison to infliximab [ 93 ]. Treatment with mycophenolate mofetil has also been described [ 94 , 95 ]. In most cases, these therapies can be discontinued within a reasonable period, but reports of treatment for an indefinite period due to persistent irAE have also been described [ 96 ].…”
Section: Treatmentmentioning
confidence: 99%